Crystal structure of 1-(4-hydroxybenzoyl)-2,7-dimethoxynaphthalene: Contribution of classical and non-classical hydrogen bonding interactions to the molecular packing structure - Okamoto, Akiko; Muto, Toyokazu; Gaowa, Siqin; Takahara, Genta; Yonezawa, Noriyuki (European Journal of Chemistry, 2017)
Crystal structure of 1-(4-hydroxybenzoyl)-2,7-dimethoxynaphthalene, C19O4H16, is reported from the viewpoint of characteristics in the helical alignments and difference compared to the crystal structure of a structural isomeric compound. The asymmetric unit of title compound contains two conformers A and B. Furthermore, the molecules in crystal exhibit atropisomerism brought about by molecular stereogenic axis of carbon-carbon bond between the carbonyl moiety and the naphthalene ring. Therefore, a pair of R- and S-enantiomeric molecules exists for each conformer. The two pairs of the enantiomeric molecules are related by two-fold helical axis in the asymmetric unit of P21/c space group, exhibiting the number of molecules is eight, Z = 8. Single molecular structure of title compound shows non-coplanarly accumulated aromatic-rings structure. The molecular packing structure is mainly stabilized non-classical hydrogen bonds involving C-H…O hydrogen bonds and C-H…π ones, however O-H…O=C classical hydrogen bonds are solely formed between same configured conformers. Comparison with the spatial alignment of an isomeric homologue, 2-hydroxy-1-(4-methoxy benzoyl)-7-methoxynaphthalene, has clarified that substitution position of hydroxy group determines not only direction of classical hydrogen bonds but also total feature of molecular packing, i.e., the homologous compound, which has hydroxy group at 2-position of naphthalene core forms intramolecular O-H…O=C classical hydrogen bond, and O-H…OMe classical hydrogen bonds between opposite enantiomeric isomers. The presence/absence and direction of the predominantly strong classical hydrogen bonds govern balance of interactions of other less effective classical and non-classical hydrogen bonds in molecular packing. In homologous compound, each of non-classical hydrogen bonds between same signed enantiomeric isomers and those between opposite enantiomeric isomers demonstrates almost same distances. In title compound, both types of non-classical hydrogen bonds formed by conformer A are imbalanced. The imbalanced non-classical hydrogen bonds are adjusted and reinforced by non-classical hydrogen bonds between conformers A and B.